Differential melatonin alterations in cerebrospinal fluid and serum of patients with major depressive disorder and bipolar disorder - Bumb, Jan Malte; Findeisen, Peter; Nölte, Ingo; Leweke, F. Markus (Comprehensive psychiatry, 2016)
Background - Melatonin, which plays an important role for regulation of circadian rhythms and the sleep/wake cycle has been linked to the pathophysiology of major depressive and bipolar disorder. Here we investigated melatonin levels in cerebrospinal fluid (CSF) and serum of depression and bipolar patients to elucidate potential differences and commonalities in melatonin alterations across the two disorders. - Methods - Using enzyme-linked immunosorbent assays, CSF and serum melatonin levels were measured in 108 subjects (27 healthy volunteers, 44 depressed and 37 bipolar patients). Covariate adjusted multiple regression analysis was used to investigate group differences in melatonin levels. - Results - In CSF, melatonin levels were significantly decreased in bipolar (P<0.001), but not major depressive disorder. In serum, we observed a significant melatonin decrease in major depressive (P=0.003), but not bipolar disorder. No associations were found between serum and CSF melatonin levels or between melatonin and measures of symptom severity or sleep disruptions in either condition. - Conclusion - This study suggests the presence of differential, body fluid specific alterations of melatonin levels in bipolar and major depressive disorder. Further, longitudinal studies are required to explore the disease phase dependency of melatonin alterations and to mechanistically explore the causes and consequences of site-specific alterations.
Gesehen am 04.07.2019